Design of Web-Based Applications of Marketing at PT Nuansa Cerah Informasi - Brian Prima Anggara; Pantjawati Sudarmaningtyas; Marya Mujayana (Jurnal Sistem Informasi Universitas Dinamika, 2016)
PT Nuansa Cerah Informasi (NCI) a company working in the field of service and software sales. Marketing department have several methods in marketing the product that are methods by by telephoning, sending letters, and holding an event or a workshop. In the method by telephoning and sending letters, the marketing department still has poor documentation, so that customers get the same letter of offer and the same promotion from marketing department. In addition, marketing manager can not find out about the achievements of results to get the cooperation agreement quickly and easily. To overcome those problems, it needs a design system which can help improve the documentation of the product marketing activities from the activities of product offerings up to getting the cooperation agreement. From the result of the test, the application can help improve the documentation of the product marketing activities and generate generate the latest reports of product marketing and target achievement from marketing activities.Keyword: marketing, agreement of cooperation